Asuhan Keperawatan Pada Ny.T Dengan Gangguan Sistem Endokrin: Diabetes Melitus Di Ruang Dahlia RSUD dr. Soeselo Kabupaten Tegal - Elen Rosalina; Esti Nur Janah; Wawan Hediyanto (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
The world is facing a triple burden caused by various disease problems. These problems include the presence of New Emerging and Re-Emerging Infectious Diseases such as Covid 19, Non-Communicable Diseases (NCDs) tend to increase every year and Infectious diseases that have not been resolved properly. This causes Indonesia to only focus on curative health efforts (Nina et al, 2018). Non-Communicable Diseases (NCDs) such as heart disease, stroke. cancer, chronic respiratory diseases and diabetes are the main causes of death in the world (WHO, 2018). Non-Communicable Diseases (NCD) or Non-Communicable Diseases (NCD) are diseases that cannot be transmitted from person to person, whose development progresses slowly over a long period of time (chronic). Non-Communicable Diseases (NCDs), also known as chronic diseases, tend to last a long time and are the result of a combination of genetic, physiological, environmental and behavioral factors (WHO, 2018).